2012
DOI: 10.1371/journal.pone.0029403
|View full text |Cite
|
Sign up to set email alerts
|

Microallopatry Caused Strong Diversification in Buthus scorpions (Scorpiones: Buthidae) in the Atlas Mountains (NW Africa)

Abstract: The immense biodiversity of the Atlas Mountains in North Africa might be the result of high rates of microallopatry caused by mountain barriers surpassing 4000 meters leading to patchy habitat distributions. We test the influence of geographic structures on the phylogenetic patterns among Buthus scorpions using mtDNA sequences. We sampled 91 individuals of the genus Buthus from 51 locations scattered around the Atlas Mountains (Antiatlas, High Atlas, Middle Atlas and Jebel Sahro). We sequenced 452 bp of the Cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 27 publications
1
28
0
1
Order By: Relevance
“…For example, geographic heterogeneity has been shown to differentiate the singular Buthus occitanus into several cryptic lineages [5]. Other recent studies have shown the importance of mountainous terrain and riverine barriers on the diversification of scorpions [6][9]. These recent studies also illustrate the impact of molecular taxonomy in revealing patterns of diversity unrepresented through traditional morphological analyses.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…For example, geographic heterogeneity has been shown to differentiate the singular Buthus occitanus into several cryptic lineages [5]. Other recent studies have shown the importance of mountainous terrain and riverine barriers on the diversification of scorpions [6][9]. These recent studies also illustrate the impact of molecular taxonomy in revealing patterns of diversity unrepresented through traditional morphological analyses.…”
Section: Introductionmentioning
confidence: 88%
“…A 1450-bp portion of the mitochondrial Cytochrome Oxidase I (COI) was amplified with primers described in Folmer et al [31], Gantenbein & Largiadér [29] and Valdez-Cruz et al [17]: LCO 1490 (Forward primer) 5'- GGT-CAA-CAA-ATC-ATA-AAG-ATA-TTG-G-3' & COI –N- 2983 (Reverse Primer) 5'-CTT-AAT-AAC-AGC-TAC-AAG-ATG-G-3'. This molecular marker appears well suited for discriminating intraspecific variation among scorpion [5], [6], [9], [10].…”
Section: Methodsmentioning
confidence: 99%
“…Thus, our second aim (2) was to test the hypothesis that divergence influenced by the Amu Darya River was simultaneous in other co-distributed species, for example potentially caused by a single vicariant event, such as initial establishment of a stable river causeway or increased flow rates. Our third goal (3) was to use genetic data to determine whether M. gorelovi contains any additional cryptic diversity, as the discovery of cryptic species is a common outcome in phylogeographic studies of scorpions (Bryson et al, 2013;Bryson, Wood, Graham, Soleglad, & McCormack, 2018;Fet, Graham, Webber, & Blagoev, 2014;Gantenbein, Fet, & Barker, 2001;Gantenbein, Soleglad, Fet, Crucitti, & Fet, 2002;Habel et al, 2012;Parmakelis, Kotsakiozi, Stathi, Poulikarakou, & Fet, 2013;Sousa, Froufe, Alves, & Harris, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This differentiation has likely evolved during long geographic separation between the two continents, which were only connected during the Messinian salinity crisis 5.9–5.3 million years before present (Manzi et al ., ). Genetic imprints of that period, or even older, were detected in many animal groups (Habel et al ., with references therein). The minimum current distance between Africa and Europe is about 15 km at the Strait of Gibraltar, a relatively short sea barrier considering the dispersal abilities of many organisms, in particular flying insects (Fig.…”
Section: Discussionmentioning
confidence: 99%